The Influence Of Organizational Culture And Career Development On Civil Servants' Motivation In The Police Unit Civil Servants Of West Kalimantan Province - Riska Riska; Arninda Arninda (UNIVED Press, 2025)
This study aims to determine the influence of Organizational Culture and Career Development on Employee Motivation at the Civil Service Police Unit of West Kalimantan Province. This study uses a quantitative strategy with an associative research design as methodology. In 2024, as many as 106 people permanent employees of the West Kalimantan Province Civil Service Police Unit were interviewed and data collection was carried out using a qustionnaire method with a saturated sample approach. The criteria studied were X1, namely Organizational Culture, X2 and Y, namely Employee Motivation. Data analysis used was validity and realibility tests, classical assumption tests such as linearity and normality, correlation and determination coefficients, F tests for simultaneous and partial effects, and multiple linier regression. Simultaneous analysis (F test) showed that Motivation (Y) was positively and significantly influenced by Organizational Culture (X1) and Career Development (X2). A favorable and statistically significant relationship between Organizational Culture (X1) and Career Development (X2) and Motivation (Y) was found in the partial test (T test).